An Incredible Story on the Credibility of Stories: Coherence, Real-Life Experience, and Making Sense of Texts in a Jaina Narrative - Ramot, Itamar (Religions, 2024)
Throughout the centuries, Jaina authors actively engaged in producing their own versions of stories that were told in sources such as the Rāmāyaṇa, Mahābhārata, and the purāṇas. These authors self-consciously present themselves as correcting preceding narratives that they do not accept as credible. However, the question arises: what criteria determine the credibility of one version over another? This paper offers one possible answer as it appears in the Investigation of Dharma (Dharmaparīkṣā), a Jaina narrative that has been retold repeatedly in different languages throughout the second millennium. By examining its earliest available retellings—in Apabhramsha (988 CE) and Sanskrit (1014 CE)—I argue that this narrative traces the credibility of stories to the ideas of (1) coherence across textual boundaries and (2) correspondence with real-life experience. In this paper, I trace how these notions manifest in the Investigation and analyze the narrative’s mechanism for training its audience to evaluate for themselves the credibility of stories. Through this analysis, the paper offers a fresh perspective on the motivations of premodern South Asian authors to retell existing narratives and sheds light on the reading practices they expect from their audience.